IMPLEMENTASI APLIKATIF KURIKULUM PAI DAN BUDI PEKERTI DI MTS - Ivana Maulia Rahmah; Suparjo (STKIP Subang, 2025)
The Islamic Religious Education (PAI) curriculum at the Madrasah Tsanawiyah (MTs) level has an important role in shaping the character and morals of students since adolescence. However, along with the development of the era and increasingly complex social challenges, the existing curriculum needs to be developed to be more relevant to the needs of today's students. This article aims to examine how the PAI curriculum at MTs can be developed with a more contextual, adaptive approach, and in accordance with technological developments and student character. The method used in this writing is a case study by reviewing various sources of literature and applicable curriculum documents. The results of the study show that in its development, the PAI curriculum at MTs has a good impact such as students' ability to read, understand, and interpret the contents of the Qur'an and Hadith. In addition, in terms of attitude and personality, students show more religious behavior and good character.